Histopathological profile of ovarian tumours: A twelve year institutional experience - Deepti Vijay Mankar; Gaurav K Jain (Wolters Kluwer Medknow Publications, 2015)
Context: Ovarian tumours represent about 30% of all cancers of the female genital system. They manifest in a wide spectrum of clinical, morphological and histological features. Aim: To study the frequency of incidence of different histopathological types of ovarian tumours in our institute. Materials and Methods: This retrospective study included 257 cases of histopathologically proven ovarian tumours, reported in the Department of Pathology of a rural tertiary care referral hospital, over a 12 year period (January 2000 to December 2011). These were classified according to the WHO classification of ovarian tumours (2003). Clinical presentation of the patients was analysed from archived case records. Results: Of the 257 tumours studied, 162 (63.04%) were benign, 15 (5.84%) were borderline and 80 (31.12%) were malignant. Surface epithelial tumours were the most common (68.48%) followed by germ cell tumours (15.95%). Mucinous cystadenomas (32.69%) were the most common benign tumours, while serous cystadenocarcinomas (31.13%) were the most common malignant tumours. Most ovarian neoplasms (43.19%) occurred in the 21-40 years age-group. Dull abdominal pain was the most common clinical presentation. Conclusions: Benign ovarian tumours were more common than malignant ones across all age groups. Surface epithelial tumours were the most common histopathological type of ovarian tumour. Due to vague symptoms, patients present late. Development of methods for early diagnosis of ovarian neoplasia is therefore, a pressing need today. The relative frequency of incidence of different ovarian tumours shows regional variations, highlighting the need to identify region-specific risk factors.